Development of a Cover System Design for Potentially Acid-Forming Tailings at Peak Gold Mines - C Silveira; C Ellice; D Christensen; M (The Australasian Institute of Mining and Metallurgy, 2003)
Peak Gold Mines (PGM), a member of the Rio Tinto Group, is an underground and open cut gold mining operation located near Cobar, NSW. A multi-phase study was initiated in 2001 in support of developing a dry æmoisture store and releaseÆ cover system design for the PGM tailings dam, which contains potentially acid-forming tailings material. The first phase consisted of characterising the tailings and potential cover material (waste rock from an open cut operation) as well as soil-atmosphere cover design modelling. The second phase involved construction of two cover system field trials on the tailings dam and installation of a variety of field instruments to monitor the hydraulic performance of the test covers during all seasons of the year. Field performance monitoring commenced in April 2002 and will continue for a minimum of two wet-dry climate cycles (third phase), prior to using the field data for calibration and subsequent validation of numerical models developed for the cover system trials (fourth phase). This paper describes the work completed for the first two project phases and also discusses the initial performance of the cover system trials.